TRANSFORMATION OF TRIPLE TALAQ (IRREVOCABLE DIVORCE) LAW IN ISLAMIC FAMILY LAW SYSTEM OF INDIA - Ahmad Zikriandi (Familia: Jurnal Hukum Keluarga, 2025)
Constitutionally, India adheres to the principle of secularism while still allowing religious communities to apply their respective laws in private matters. For Muslims, these provisions are regulated under the Muslim Personal Law (Shariat) Application Act, 1937. In practice, however, the implementation of this law faces challenges due to strong social and patriarchal influences. One of the most controversial issues is the practice of triple talaq, which has led to gender inequality. This study aims to analyze the process of legal transformation of triple talaq within Islamic family law in India and the implications of its prohibition. Using a qualitative method with a normative-juridical approach, this research examines primary legal sources and academic literature. The theory used in this study is the theory of legal pluralism. The findings reveal that the reform of Islamic family law in India has been a long process beginning with the Shah Bano case (1985) and the Muslim Women Act (1986), evolving through the Dania Latifi case (2001), and culminating in the Shayara Bano judgment (2017), which reinforced the prohibition of triple talaq. This transformation signifies a shift from the dominance of traditional fiqh toward a national legal system oriented toward justice and the protection of Muslim women.